Earthquakes From Tectonics to Buildings - Salazar, Walter (Earthquakes, 2021)
Earthquakes - From Tectonics to Buildings is a compilation of eight chapters that explain tectonics and seismicity. The book presents state-of-the-art techniques for calculating ground motion amplification due to sediments above the engineering bedrock employing strong-motion recordings and microtremor data. It also explains liquefaction phenomena through interpretive structural modeling techniques. Finally, the book presents pile foundations' seismic behavior on liquefiable soils and remedial countermeasures against earthquake attacks.